Determinan Kepatuhan Wajib Pajak Sektor Telekomunikasi Usaha Kecil Menengah di Sumatera Barat - Angga Pebri Ardimis; Aries Tanno (Jurnal Ecogen, 2021)
This study aims to identify the factors that influence the compliance of MSME taxpayers in the telecommunications sector in West Sumatra. In particular, this study seeks to empirically examine the effect of tax rates, socialization, tax sanctions, and understanding of taxation on the level of taxpayer compliance. This research is quantitative, sourced from primary data obtained from taxpayers of SMEs in the Telecommunication Sector in West Sumatra. The sample of this study consisted of 40 compulsory people. This study found that tax sanctions and understanding of taxation have a positive effect on taxpayer compliance. Meanwhile, tax rates and socialization do not affect the level of compliance. Regardless of the applicable tax rate, taxpayers will automatically pay taxes at whatever tax rate level is following their income. In contrast, the socialization carried out is still classified as having a short duration, so that it is difficult for respondents to pay taxes. Understand socialization. Practically this research can contribute to the preparation of regulations regarding the calculation and collection of value-added tax and income tax on income in connection with the sale of credit, starter packs, tokens, and vouchers; it is necessary to review the regulations issued and effective in a short period so that taxpayers have not fully understood the socialization of this policy.